2009
DOI: 10.2503/hrj.8.309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red-light Intensity during Long-day Treatment on Flowering and Cut Flower Quality in Eustoma grandiflorum Cultivars for Early-autumn Shipment

Abstract: Long-day treatment by pre-dawn lighting (6 h) was applied to Eustoma grandiflorum cultivars to investigate flowering responses and cut flower qualities for early-autumn shipment. Seedlings were irradiated by using bulb-type red-light fluorescent lamps, that R : FR ratio was 8.8, with photon flux density (PFD) of red-light (660 ± 30 nm) of 0.1, 0.2 or 0.5 µmol・m −2 ・s −1 .Control plants were grown under ambient day conditions of 14-15 h without long-day treatment. The times from planting to flower budding under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…This observation is consistent with the finding that using INC (with low R:FR ratio) as a light source for NI hastens flowering in petunia and Coreopsis grandiflora (Runkle et al, 2012). Sato et al (2009) and Yamada et al (2009aYamada et al ( , 2009b also showed that flowering in Eustoma is promoted when the R:FR ratio of the NI light source is low. In the current study, regression analysis between days to first flower and spectral factors (Table 4) We observed the flowering responses of petunia to growth under artificial light sources for 10 weeks (Table 3), finding that all plants grown under all light sources flowered, except FL tube, which induced flowering in only 20% of petunia plants.…”
Section: Effects Of Artificial Light Sources On Flowering Responsessupporting
confidence: 91%
See 2 more Smart Citations
“…This observation is consistent with the finding that using INC (with low R:FR ratio) as a light source for NI hastens flowering in petunia and Coreopsis grandiflora (Runkle et al, 2012). Sato et al (2009) and Yamada et al (2009aYamada et al ( , 2009b also showed that flowering in Eustoma is promoted when the R:FR ratio of the NI light source is low. In the current study, regression analysis between days to first flower and spectral factors (Table 4) We observed the flowering responses of petunia to growth under artificial light sources for 10 weeks (Table 3), finding that all plants grown under all light sources flowered, except FL tube, which induced flowering in only 20% of petunia plants.…”
Section: Effects Of Artificial Light Sources On Flowering Responsessupporting
confidence: 91%
“…Light conditions in which relatively high levels of FR are provided by HL are highly similar to shade produced by a plant canopy, which increases apical dominance and suppresses branching (Smith and Whitelam, 1997;Tucker, 1975). In the current study, the number of lateral branches also increased under the light source with the highest ratio of R:FR (Table 1 and Table 2), which is similar to the findings of Yamada et al (2009b), who showed that the number of branches in E. grandiflorum increased with increasing R ratio.…”
Section: Effects Of Artificial Light Sources On Growth Responsessupporting
confidence: 89%
See 1 more Smart Citation
“…There is no agreed-upon convention in the scientific community for measuring and reporting R:FR. In particular, there are wide variations in specific wave bands and the units of measure used to calculate the ratio (Blom and Kerec, 2003;Capers and Chazdon, 2004;Clifford et al, 2004;Erwin et al, 2006;Feldhake and Glenn, 1997;Mata and Botto, 2009;Pecot et al, 2005;Turnbull and Yates, 1993;Yamada et al, 2009;Yang et al, 2012). When discussing this issue with various delegates at the 2012 International Symposium on Horticultural Lighting, it became clear that there is a need for consensus among researchers in order for direct comparisons to be made in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Since plants readily absorb red light (used in photosynthesis) but transmit or reflect far red light, the R:FR decreases within dense canopies or below an upper layer of foliage (e.g., a forest understory). The R:FR of ambient sunlight is generally between 1.0 and 1.2, although this varies considerably in the literature depending on location and how the ratio is calculated (Blom and Kerec, 2003;Clifford et al, 2004;Erwin et al, 2006;Feldhake and Glenn, 1997;Mata and Botto, 2009;Smith, 1982;Turnbull and Yates, 1993;Yamada et al, 2009;Yang et al, 2012). When exposed to subambient R:FR, many common floriculture plants will shift their morphological development toward growing taller in an effort to access direct light.…”
mentioning
confidence: 99%